Comparison of peripheral intravenous catheterization applied to different anatomical sites in terms of pain, phlebitis and infiltration - Feride Kaplan; Hanife Çelik; Hakime Aslan; Seher Çevik Aktura (BMC Nursing)
Abstract Aim This study was conducted to compare peripheral intravenous catheterization (PIVC) at different anatomical sites in terms of pain, phlebitis and infiltration. Material and methods The study was a comparative-descriptive study. The population of the study consisted of all adult patients being treated and receiving intravenous drug therapy in a state hospital. The sample of the study consisted of a total of 154 patients who met the inclusion criteria for the study and were selected by non-probability sampling method. The “Patient Information Form” created by the researchers, “Phlebitis and Infiltration Scale” and “Visual Analogue Scale (VAS)” were used to collect data. Results In the study, it was determined that there was no significant difference between the degree of phlebitis, time of phlebitis and degree of infiltration between the PIVC applied upper hand, forearm and antecubital regions (p > 0.05), but there was a significant difference between the regions in terms of pain (p < 0.05). It was determined that the severity of pain upper hand was significantly higher than the other groups. Conclusion PIVC’s applied at different anatomical sites were similar in terms of the risk of phlebitis and infiltration, but pain intensity was much higher upper hand. It has been determined that various factors related to the patient, nurse and other variables affecting the level of phlebitis, infiltration and pain are effective.